THE CORRELATION BETWEEN STUDENTS’ GRAMMAR MASTERY AND THEIR PERFORMANCE IN WRITING DESCRIPTIVE TEXT AT THE TENTH CLASS OF SMK MUHAMMADIYAH 1 METRO ACADEMIC YEAR 2012/2013 - Een - Fariyanti; Eva - Faliyanti (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2013)
Writing is a language skill that is used for indirect communication to convey a message or information to the readers. In writing a text, we can explore our ideas, feelings and thoughts which are arranged in words, sentences, and paragraph by using eyes, brain and hand. In writing a text, we must be able to use a good language and we also must be able to arrange good sentences grammatically in order the readers understand about the content of our writing. Besides that, if the students will make a sentences or paragraph, they must have knowledge about tenses. The objectives of the research are to find out the students’ simple grammar mastery and their performance in writing descriptive and also to find out whether or not there is a correlation between the students’ grammar mastery and their performance in writing descriptive. The subjects of this research are the tenth grade of SMK Muhammadiyah 1 Metro (class XA1 and class XAP). In this research, the writer used descriptive quantitative method because the final score of variable is number and the analysis is using statistic. The researcher tried to analyze the current data about students’ grammar mastery and their performance in writing descriptive. In collecting data, the researcher administered two kinds of test. They are simple present tense test and writing test. The simple present tense test are consists of 20 items of multiple choice and the writing test, the students choose one of topics from three topics. The result of this research shows that the students’ simple present tense mastery was middle. It can be seen from the average of simple present tense test is 70.6. The students’ performance in writing descriptive was middle. It can be seen from the average of writing descriptive test is 74.9. The conclusion above was from result of data analysis, it was found that writing descriptive affected by simple present tense mastery.